Molecular mechanism of autophagy in porcine reproductive and respiratory syndrome virus infection - Chen, Xiaoyong; Yu, Ziding; Li, Wenfeng (Frontiers in Cellular and Infection Microbiology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV), a significant pathogen affecting the swine industry globally, has been shown to manipulate host cell processes, including autophagy, to facilitate its replication and survival within the host. Autophagy, an intracellular degradation process crucial for maintaining cellular homeostasis, can be hijacked by viruses for their own benefit. During PRRSV infection, autophagy plays a complex role, both as a defense mechanism of the host and as a tool exploited by the virus. This review explores the current understanding of the molecular mechanisms underlying autophagy induction under PRRSV infection, its impact on virus replication, and the potential implications for viral pathogenesis and antiviral strategies. By synthesizing the latest research findings, this article aims to enhance our understanding of the intricate relationship between autophagy and PRRSV, paving the way for novel therapeutic approaches against this swine pathogen.